Citizenship in Organizations Practicing the Immeasurable (Springer International Publishing, 2018)
This book brings together a wide variety of meta-reflections on shifts in economy, power relations and organizing in confrontation with practices of citizenship. The focus is directed towards the position of (im)measurability of certain changes on meta-level within (organized) practices of citizenship. The organization or 'organizing' is the turntable, the metaphor, through which we can exemplify the emergence of growing citizen consciousness. In short, we see 'organizing' as the central metaphor wherewith the shift of the societal paradigm can be tested/verified/examined. In this book, different perspectives shall be represented on how people develop through organizing. It is more or less a residue of invisible processes that take place in and with people, through changes in discourses and in founding new types of communities and networks such as the creation of alternative local (exchange)trade opportunities. Citizenship implies exercise. On behalf of their experience with, through or while working in an organization, people 'make' their own membership of a community, an organization and/or a society.